Assessment of Extracellular Cytokines in the Hippocampus of the Awake Behaving Rat Using Large‐Molecule Microdialysis Combined with Multiplex Arrays After Acute and Chronic Ethanol Exposure. (11th February 2019) - Gano, Anny; Vore, Andrew S.; Sammakia, Maryam N.; Deak, Terrence
Abstract : Background: Studies have demonstrated persistent changes in central nervous system (CNS) cytokine gene expression following ethanol (EtOH) exposure. However, the low endogenous expression and short half‐lives of cytokines in the CNS have made cytokine protein detection challenging. The goal of these studies was to establish parameters for use of large‐molecule microdialysis and sensitive multiplexing technology for the simultaneous detection of brain cytokines, corticosterone (CORT), and EtOH concentrations in the awake behaving rat. Methods: Adult (P75+) male Sprague Dawley rats that were either naïve to EtOH (Experiment 1) or had a history of adolescent chronic intermittent EtOH (CIE; Experiment 2) were given an acute EtOH challenge during microdialysis. Experiment 1 examined brain EtOH concentrations, CORT and a panel of neuroimmune analytes, including cytokines associated with innate and adaptive immunity. The natural time course of changes in these cytokines was compared to the effects of an acute 1.5 or 3.0 g/kg intraperitoneal (i.p.) EtOH challenge. In Experiment 2, rats with a history of adolescent CIE or controls exposed to vehicle were challenged with 3.0 g/kg i.p. EtOH during microdialysis in adulthood, and a panel of cytokines was examined in parallel with brain EtOH concentrations and CORT. Results: The microdialysis procedure itself induced a cytokine‐specific response that replicated across studies, specifically a sequential elevation of interleukin‐6 (IL‐6), tumor necrosis factor alpha (TNF‐α), and IL‐10. Surprisingly, acute EtOH did not significantly alter this course of cytokine fluctuations in the hippocampus. However, a history of adolescent CIE showed drastic effects on multiple neuroimmune analytes when rechallenged with EtOH as adults. Rats with a history of adolescent EtOH displayed a severely blunted neuroimmune response in adulthood, evinced by suppressed IL‐1β, IL‐10, and TNF‐α. Conclusions: Together, these findings provide a methodological framework for assessment of cytokine release patterns, their modulation by EtOH, and the long‐lasting changes to neuroimmune reactivity evoked by a history of adolescent CIE. Abstract : These studies utilized the novel combination of large molecule microdialysis with high sensitivity multiplexing to pursue prolonged timecourse analyses of cytokine protein in the hippocampus. These data established a normative range for examining cytokines using this technique and indicated that neither a low nor high dose ethanol challenge (1.5, 3.0 g/kg i.p.) had a profound effect on their concentrations. However, a history of chronic adolescent ethanol significantly impaired the ability of multiple cytokines to respond to an adult ethanol challenge.